Heterogeneous adjustments of employment to automation technologies: Evidence from manufacturing industries in European regions - Tommaso Ciarli; Florencia Jaccoud; Fabien Petit (EconPol Forum, 2022)
Employment adjustments to automation vary across industries, regions, technologies, and time. Technological penetration of robots is related to higher employment within the industry in low-tech regions in the short run. Robots are negatively correlated to employment in knowledge-intensive regions. Regional heterogeneity in employment adjustment to robots is not driven by industry composition. High-tech industries adjust employment to ICT penetration faster than low-tech industries.
Keywords: 330